2020
DOI: 10.48550/arxiv.2006.02770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics of Dataset Retrieval Sessions: Experiences from a Real-life Digital Library

Zeljko Carevic,
Dwaipayan Roy,
Philipp Mayr

Abstract: Secondary analysis or the reuse of existing survey data is a common practice among social scientists. Searching for relevant datasets in Digital Libraries is a somehow unfamiliar behaviour for this community. Dataset retrieval, especially in the social sciences, incorporates additional material such as codebooks, questionnaires, raw data files and more. Our assumption is that due to the diverse nature of datasets, document retrieval models often do not work as efficiently for retrieving datasets. One way of en… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…They concluded their study by drawing clear differences between the search for dataset compared to publication; firstly, the average number of record views in dataset search sessions was significantly lower compared to sessions searching for publications. Secondly, similar to Kacprzak et al (2018), they reported difficulty in understanding the users' intent and their differences between dataset search and publication search, due to the minor differences between the two sets of queries (Carevic et al, 2020).…”
Section: Dataset Searchmentioning
confidence: 95%
See 4 more Smart Citations
“…They concluded their study by drawing clear differences between the search for dataset compared to publication; firstly, the average number of record views in dataset search sessions was significantly lower compared to sessions searching for publications. Secondly, similar to Kacprzak et al (2018), they reported difficulty in understanding the users' intent and their differences between dataset search and publication search, due to the minor differences between the two sets of queries (Carevic et al, 2020).…”
Section: Dataset Searchmentioning
confidence: 95%
“…Nevertheless, in both of the setting having individuals searching for datasets, neither set necessarily represented how individuals would like to search for data. Carevic et al (2020) focused on characterising the users' intents when performing publication (document) search and research datasets in a Digital Library for the social sciences discipline. They studied all the user log data for an entire year, and extracted sessions that searched only for datasets and publications.…”
Section: Dataset Searchmentioning
confidence: 99%
See 3 more Smart Citations